2002
DOI: 10.1074/jbc.m206376200
|View full text |Cite
|
Sign up to set email alerts
|

N-Ethylmaleimide Inhibits Platelet-derived Growth Factor BB-stimulated Akt Phosphorylation via Activation of Protein Phosphatase 2A

Abstract: The redox state plays an important role in gene regulation. Thiols maintain the intracellular redox homeostasis. To understand the role of thiols in redox signaling, we have studied the effect of thiol alkylation on platelet-derived growth factor-BB (PDGF-BB)-induced cell survival events in vascular smooth muscle cells. PDGF-BB stimulated Akt phosphorylation predominantly at Ser-473. N-Ethylmaleimide (NEM), a thiol alkylating agent, blocked PDGF-BB-induced Akt phosphorylation without affecting its upstream pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 62 publications
2
80
0
Order By: Relevance
“…23 The activation of PP2A by N-ethylmaleimide, ceramide, palmitate or integrin a2b1 inhibits Akt phosphorylation. [23][24][25][26] Conversely, the inhibition of PP2A by okadaic acid increases Akt activities. 21,25,26 Previously, we and others found that expression of caveolin-1 (cav-1), the major component of caveolae, is elevated in prostate cancer and other malignancies.…”
Section: Mechanisms Of Akt Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The activation of PP2A by N-ethylmaleimide, ceramide, palmitate or integrin a2b1 inhibits Akt phosphorylation. [23][24][25][26] Conversely, the inhibition of PP2A by okadaic acid increases Akt activities. 21,25,26 Previously, we and others found that expression of caveolin-1 (cav-1), the major component of caveolae, is elevated in prostate cancer and other malignancies.…”
Section: Mechanisms Of Akt Regulationmentioning
confidence: 99%
“…98,107,108 In the past few years, the results of multiple studies have shown that PP2A or PP1 can participate in the regulation of PI3-K-Akt pathway through dephosphorylation of activated Akt and that these proteins can function as the major phosphatases for Akt in some systems. [21][22][23][24][25][26] Recent studies also show that alteration of PP2A and PP1 gene expression is associated with multiple human cancers. The PP2R1B gene that encodes the b isoform of the A subunit of PP2A is located in a region showing high-frequency LOH.…”
Section: Genetic Perturbation and Dysregulation Of The Pi3-k-akt Pathwaymentioning
confidence: 99%
“…Phosphorylation by Akt and SGK in response to insulin and growth factors The FoxO family is negatively regulated by the PI3K-Akt signaling pathway in response to insulin, insulinlike growth factors, growth factors and neurotrophic factors (Lin et al, 1997;Ogg et al, 1997;Brunet et al, 1999;Guo et al, 1999;Jackson et al, 2000;Medema et al, 2000;Yellaturu et al, 2002;Zheng et al, 2002). Phosphorylation of FoxO factors at three conserved sites by the protein kinases Akt and SGK (serum and glucocorticoid-induced kinase) causes the sequestration of FoxO factors in the cytoplasm, thereby preventing FoxO factors from transactivating their target genes (Figures 2 and 3) (Biggs et al, 1999;Brunet et al, 1999Brunet et al, , 2001Kops et al, 1999;Nakae et al, 1999).…”
Section: Relocalization Of Foxo From the Nucleus To The Cytoplasmmentioning
confidence: 99%
“…NEM appears to produce reactive oxygen species (ROS) in various cells (Leoncini and Signorello, 1999b;Meves et al, 2001;Yellaturu et al, 2002). Particularly, NEM has been reported to generate ROS by activation of membrane-bound NADPH oxidase which is known to exist in HepG2 cells (Ehleben et al, 1997;Cool et al, 1998).…”
Section: Discussionmentioning
confidence: 99%